Acute Bilateral Simultaneous Optic Neuritis - Maxner, Charles E.; Ramsey, Kevin M. (DALHOUSIE MEDICAL JOURNAL, 2003)
Background: Acute bilateral simultaneous optic neuritis (ABSON) without a prior neurological history is a rare clinical problem, and little is known about its prognosis for visual recovery and for the development of multiple sclerosis (MS). Methods: We conducted a case review of six patients who presented with ABSON from 1986-98, and did a follow-up on their present medical status. The results were compared to similar case reviews, and to the unilateral Optic Neuritis Treatment Trial. Results: All six patients went on to recover normal vision. One of the six patients (16.7%) reviewed went on to develop probable MS. Interpretation: This low association with MS is in agreement with other case reports of ABSON. ABSON appears to have a significantly better prognosis for not developing neurological disease than unilateral optic neuritis. In particular, patients with ABSON without associated systemic symotoms tend to recover quickly to normal health.